Ultrasound methods of imaging atherosclerotic plaque in carotid arteries: examinations using contrast agents - Fedak, Andrzej (J Ultrason, 2020)
The primary technique for detecting the presence and monitoring the development of carotid atherosclerotic plaque is ultrasound. The development of ultrasound techniques has made it possible to precisely visualise not only blood flow, but also vessel walls, including atherosclerotic plaque. Contrast-enhanced ultrasound examination enables one to make an objective observation of atherosclerotic plaque neovascularisation, clearly indicating active inflammation, which is an inherent feature of vulnerable (unstable) plaque. Depending on the examination method used, it is possible to precisely visualise different components of the plaque and its behaviour during blood flow through the vessel lumen or through the neovessels of the plaque, and, consequently, determine the possible presence of inflammation, which is a defining feature of plaque stability. The full utilisation of physical phenomena that underlie contrast-enhanced ultrasound will bring further enormous progress of diagnostic and probably also therapeutic methods for carotid atherosclerosis. The selection of the right examination method significantly accelerates diagnosis and adequate classification of plaque, and makes it possible to monitor the progression of atherosclerosis. However, one needs to bear in mind that ultrasound remains a very subjective method. The success of contrast-enhanced ultrasound also depends on the skills and experience of the examiner. Current attempts at increasing the objectivity of contrast-enhanced ultrasound examination using artificial intelligence will make it possible in the future to make a definitive evaluation of atherosclerotic plaque stability. This will allow one to assess the risk of ischaemic stroke adequately.